Mapping law enforcement challenges in money politics during regional head elections in Indonesia: A scoping review - Indahwati Indahwati; Muhammad Chardijana; Fredy Johari Andiansah (Journal of Law Science, 2026)
Money politics continues to undermine the integrity of regional head elections in Indonesia, reflecting persistent weaknesses in election law enforcement. While existing studies discuss vote buying, comprehensive reviews assessing enforcement effectiveness remain limited. This study aims to map scholarly research on money politics in regional elections and identify key enforcement challenges. Using a scoping review based on the Arksey and O’Malley framework, this study analyzes 10 journal articles published between 2020 and 2024 from SINTA, Scopus, and DOAJ, employing thematic content analysis. The findings indicate that money politics persists due to weak institutional coordination, high evidentiary standards, short handling timelines, and pragmatic voter behavior. Law enforcement largely targets field-level actors, resulting in a low deterrent effect. This study contributes by identifying regulatory and institutional gaps and offering policy-relevant insights to strengthen election law enforcement and electoral integrity in Indonesia.